2000
DOI: 10.1038/82199
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of HIV-1 Tat protein mediated by low-density lipoprotein receptor-related protein disrupts the neuronal metabolic balance of the receptor ligands

Abstract: Neurological disorders develop in most people infected with human immunodeficiency virus type 1 (HIV-1). However, the underlying mechanisms remain largely unknown. Here we report that binding of HIV-1 transactivator (Tat) protein to low-density lipoprotein receptor-related protein (LRP) promoted efficient uptake of Tat into neurons. LRP-mediated uptake of Tat was followed by translocation to the neuronal nucleus. Furthermore, the binding of Tat to LRP resulted in substantial inhibition of neuronal binding, upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
316
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 355 publications
(331 citation statements)
references
References 44 publications
(63 reference statements)
12
316
0
2
Order By: Relevance
“…However, our data contradict other studies on TAT-peptide-mediated protein transduction (Mann and Frankel, 1991;Derossi et al, 1996;Vivès et al, 1997;Elliott and O'Hare, 1997) and TAT-phage-mediated gene transfer (Eguchi et al, 2001) that do not depend on endosomotrophic reagents. The mechanism of action of Tat-(48 -60) peptide and the full-length Tat protein may not be the same (Liu et al, 2000). Rather, TAT-pK-mediated gene transfer seems to share features of both systems, operating by both an energy-dependent endocytic pathway and an independent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, our data contradict other studies on TAT-peptide-mediated protein transduction (Mann and Frankel, 1991;Derossi et al, 1996;Vivès et al, 1997;Elliott and O'Hare, 1997) and TAT-phage-mediated gene transfer (Eguchi et al, 2001) that do not depend on endosomotrophic reagents. The mechanism of action of Tat-(48 -60) peptide and the full-length Tat protein may not be the same (Liu et al, 2000). Rather, TAT-pK-mediated gene transfer seems to share features of both systems, operating by both an energy-dependent endocytic pathway and an independent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Our recent studies suggest that interaction of HIV-1 Tat protein with LRP, with resulting disruption of the normal metabolic balance of LRP ligands, may contribute to AIDS-associated neuropathology including dementia. 16 These findings raise the possibility of using EGb as an alternative strategy to treat HIV-induced neurological disorders.…”
Section: Human Immunodeficiency Virus (Hiv)-1 Tat Protein Ismentioning
confidence: 97%
“…The addition of HS and the inhibitor of LRP to the culture medium produced a significant decrease in the cellular uptake of the protein. However, the uptake of the full-length Tat protein suffered a certain decrease at 4°C (16), and some energydependent endocytosis pathway seemed to play a significant role in the internalization of the Tat protein. These results suggested that the mechanisms of internalization of the Tat-(48 -60) peptide and the full-length Tat protein may not be completely parallel.…”
mentioning
confidence: 99%
“…Involvement of the cell surface heparan sulfate (HS) and low density lipoprotein receptor-related protein (LRP) was suggested in the translocation of the full-length Tat protein (16,17). The addition of HS and the inhibitor of LRP to the culture medium produced a significant decrease in the cellular uptake of the protein.…”
mentioning
confidence: 99%